Cascade utilization of exhaust gas and jacket water waste heat from an Internal Combustion Engine by a single loop Organic Rankine Cycle system - Ma, Jiacheng; Liu, Liuchen; Zhu, Tong; Zhang, Tao (Applied thermal engineering, 2016)
•A single loop ORC is proposed to recover the waste heat of exhaust and jacket water.•Energy analysis are conducted for establish the mathematical model.•System performance based on three working fluids is evaluated.•Heat exchanger performance under different part-load conditions is validated. This work presents the methodology of Internal Combustion Engine (ICE) waste heat recovery by an Organic Rankine Cycle (ORC) system. Though jacket waster heat is usually ignored due to its low temperature, the contained thermal energy is roughly the same as that of exhaust gas from an ICE with certain rated loads, which makes the recovery of this energy a subject of interest. The cascade utilization of exhaust gas and jacket water heat by single loop ORC systems is here investigated and compared with a system which only recovers exhaust gas heat. System performances are evaluated through thermal efficiency, waste heat recovery efficiency and improvement of ICE efficiency. Then the calculated heat exchanger capacity is validated under different ICE load conditions. Results show that the highest thermal efficiency (21.82%) can be reached by using R141b. The full recovery of exhaust gas heat yields the highest waste heat recovery efficiency (10.19%) and improvement of the ICE efficiency (14.23%). Preheaters and evaporators operated at high evaporating pressure may have a heat exchanger capacity which is lower than the calculated heat amount under ICE part-load conditions. It is therefore essential to validate the calculated heat exchanger capacity in real operating conditions.